Woman possibly looking at stamps in the Carnegie Library. - Unknown (Forsyth County Public Library, 1940)
Photo made in the 1940s.
Woman possibly looking at stamps in the Carnegie Library.
Keywords: Digital Forsyth; Forsyth County (N.C.) -- History -- Sources; Carnegie Library (Winston-Salem, N.C.); Forsyth County Public Library; Forsyth County (N.C.) -- History -- Pictorial works; Winston-Salem (N.C.)